THE EFFECT OF ERGONOMIC GYMNASTICS TOWARD ELDERLY SLEEP QUALITY IN BANTUL YOGYAKARTA - Sri Setyowati (Universitas Muhammadiyah Semarang, 2015)
Background: Added the age of individual is a physiological process that will occur in every human being, the aging process a person will experience a variety of sleep disorders or insomnia problems. Relaxsation progressive muscle can be done by way of ergonomic gymnastic movement conveyed by Sagiran (2013) states that the exercise is ergonomic gymnastic movement is a movement inspired by the movements as we run a prayer.Purpose: To know the ergonomic gymnastics toward elderly sleep quality in Bantul Yogyakarta. Methods: The study is quasi-experimental design with one group pretest-posttest design, intervention 6 times for 3 weeks performed every 2 weeks time. Then post test 4 weeks to measure the quality of sleep by PSQI. A sample of 15 respondents who are active in Posyandu.Results: The quality of sleep of elderly in Yogyakarta Sewon Kepek Timbulharjo prior to the ergonomics gymnastics has 13 values in 5 respondents with a percentage of 33.32%. After doing gymnastics ergonomic has 15 values in 8 respondents with a percentage 53.33%. Having tested with the Wilcoxon test values obtained significancy 0.011 (p <0.05). Conclusion: There is a ergonomic gymnastics toward elderly sleep quality in Bantul Yogyakarta.Keywords: Gymnastics Ergonomics, Sleep Quality, Elderly